Programmes’ paperwork guideline / Mohammad Amirul Anwar Badrul Hisham … [et al.] - Badrul Hisham, Mohammad Amirul Anwar; Azmi, Amirul Hakimi; Mustafa, Aaimie Maissarah; Dzulhaimi, Deanna Athirah; Shaifuddin, Mohd Shakir Ariff (Division of Research and Industry Linkages, 2017)
PROGRAMMES’ PAPERWORK GUIDELINE is an innovation by students from the Faculty of Administrative Science and Policy Studies (FSPPP). This product is a guideline that will assist the students in making paperwork for any program that will held UiTM. This product will be used by any students in campuses to have a standardized system for making paperwork for any program as it will help to guide the organizer or students to have systematic and efficient programmes in future.